One unashamed night - James, Sophia (Sophia Annie) (Harlequin historicals, 2010)
"Living in a gray world of silhouette, Lord Taris Wellingham conceals his fading eyesight from society. He has long protected himself from any intimate relationships. Plain twenty-eight-year-old Beatrice-Maude Bassingstoke does not expect to attract any man, especially not one as good-looking as her remote traveling companion. Forced by a snowstorm to spend the night together, these two lonely people seek solace in each other's arms. The passion they unleash surprises them both. Then a new day dawns..."--P. [4] of cover.